Effects of dividend tax reform on dividend behavior : a clientele theory approach - Ida Suriya Ismail,; Mohd Rizal Palil,; Rosiati Ramli,; Mara Ridhuan Che Abdul Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Clientele theory claims that investors have their own systematic preference to plan their dividend portfolios based on tax and transaction cost incurred. Due to that, companies need to decide on their dividend payout policy that can attract investors to invest in their company especially when dividend tax laws change from full imputation system to single tier tax system (STT). STT is expected to enhance the simplicity and efficiency of the tax administration process with the intention of encouraging companies to pay dividend. Therefore, this paper attempts to examine company dividend payouts by focusing on two observations periods; during transitional period of STT and after the compulsory effects of STT. This study has selected 141 public listed companies from two of the biggest industries in Malaysia and produced 4,508 observations for the period of 2002 until 2015. This study has used t-test of significant difference to test the changes on dividend payouts by splitting the data into full sample and among the payers only. Initially, during the transitional period, results were consistent with clientele theory when it was found that both regular and special dividend had significantly increased during transitional period. In addition, this study also found that companies with the best performance in terms of return on equity had significantly increased their regular dividend, while moderate companies has significantly increased special dividend during transitional period. But the results were insignificant among poor performance companies. In contrast, the results suggested that there is no significant difference of dividend payouts once the compulsory effects of STT took place.